PENGARUH DEWAN PENGAWAS SYARIAH, INTELLECTUAL CAPITAL, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA BANK SYARIAH DI INDONESIA - Zuliana, Renny; Aliamin, Aliamin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aimed to examine the effect of sharia supervisory board, intellectual capital, and corporate social responsibility toward performance of islamic bank in Indonesia. The type of research used in this study is quantitative, using secondary data. Data taken from companys financial statement and implementation report of GCG which audited of islamic bank in Indonesia during 2014-2016. In this research used purposive sampling method, 11 over 13 Islamic Banking can be used as samples. Analysis of data to test the hypothesis used multiple linear regression and are processed by SPSS 20th version program. The results of the study state that sharia supervisory board, IC, and CSR simultaneously influence the performance of Islamic banks which are proxied by ROA. Partially sharia supervisory board has a negative and significant effect on ROA, IC has a positive and significant effect on ROA. While the results of testing partially CSR does not affect ROA as a proxy for the performance of Islamic banks